Change of critical COVID-19 disease in time - DEMİR, Ufuk; SOYLU, Veysel Garani; TAŞKIN, Öztürk; YILMAZ, Ayşe (MediHealth Academy, 2022)
Background:: COVID-19 disease, which has taken over the world for more than a year, is unfortunately not yet understood and a definitive treatment has not been found. The aim of this study is to investigate the changes in clinical and laboratory tests of critical COVID-19 patients followed in the intensive care unit between March/2020 and December/2020 and to evaluate the factors that cause these changes with literature information.
Materıal and Method: In the study, during the beginning of the pandemic and its progress; 50 COVID-19 patients treated in the intensive care unit between March-April-May/2020 were defined as group 1, and 50 COVID-19 patients treated in the intensive care unit between October-November-December/2020 were defined as group 2.Clinical, laboratory and intensive care processes of the patients in the groups were analyzed retrospectively and compared.
Results:Demographic data were similar between groups. Group 2 patients had higher 28-day mortality, and this result was statistically significant (p = 0.006). Transfer rates of group 1 patients to the service after intensive care were found to be statistically higher (p = 0.029).
Conclusıons:28-day mortality was found to be different between similar patient groups who were admitted to intensive care during different periods of the pandemic. The reasons for this may be: changes in pathogenicity as a result of viral mutations, different immune responses of hosts to viral infection, intensive care experience of healthcare professionals.
Keywords: 3. Good health